Modelling of mineral dust for interglacial and glacial climate conditions with a focus on Antarctica - N. Sudarchikova; U. Mikolajewicz; C. Timmreck; D. O'Donnell; G. Schurgers; D. Sein; K. Zhang (Climate of the Past, 2015)
The mineral dust cycle responds to climate variations and plays an important role in the climate system by affecting the radiative balance of the atmosphere and modifying biogeochemistry. Polar ice cores provide unique information about deposition of aeolian dust particles transported over long distances. These cores are a palaeoclimate proxy archive of climate variability thousands of years ago. The current study is a first attempt to simulate past interglacial dust cycles with a global aerosol–climate model ECHAM5-HAM. The results are used to explain the dust deposition changes in Antarctica in terms of quantitative contribution of different processes, such as emission, atmospheric transport and precipitation, which will help to interpret palaeodata from Antarctic ice cores. The investigated periods include four interglacial time slices: the pre-industrial control (CTRL), mid-Holocene (6000 yr BP; hereafter referred to as "6 kyr"), last glacial inception (115 000 yr BP; hereafter "115 kyr") and Eemian (126 000 yr BP; hereafter "126 kyr"). One glacial time interval, the Last Glacial Maximum (LGM) (21 000 yr BP; hereafter "21 kyr"), was simulated as well to be a reference test for the model. Results suggest an increase in mineral dust deposition globally, and in Antarctica, in the past interglacial periods relative to the pre-industrial CTRL simulation. Approximately two-thirds of the increase in the mid-Holocene and Eemian is attributed to enhanced Southern Hemisphere dust emissions. Slightly strengthened transport efficiency causes the remaining one-third of the increase in dust deposition. The moderate change in dust deposition in Antarctica in the last glacial inception period is caused by the slightly stronger poleward atmospheric transport efficiency compared to the pre-industrial. Maximum dust deposition in Antarctica was simulated for the glacial period. LGM dust deposition in Antarctica is substantially increased due to 2.6 times higher Southern Hemisphere dust emissions, 2 times stronger atmospheric transport towards Antarctica, and 30% weaker precipitation over the Southern Ocean. The model is able to reproduce the order of magnitude of dust deposition globally and in Antarctica for the pre-industrial and LGM climates.